Internalization and cytotoxicity of polystyrene microplastics in human umbilical vein endothelial cells - Lu, Yan‐yang; Cao, Meiyi; Tian, Meiping; Huang, Qingyu (Journal of applied toxicology, 2023)
Ubiquitous micro(nano)plastics (MNPs) are emerging environmental pollutants, which pose a potential threat to human health. When MNPs enter the blood circulatory system, vascular endothelium is one of the most important target organs that directly interact with the MNPs. However, little is known about the cytotoxicity of MNPs to vascular endothelial cells. In this study, we investigated the uptake and cytotoxic effects of polystyrene MNPs with a particle size of 1 μm (1‐μm PS‐MNPs) on human umbilical vein endothelial cells (HUVECs) in vitro. Our study found that interaction between HUVECs and 1‐μm PS‐MNPs was at a very low level. Even at the high exposure concentration of 25 μg/mL, the percentage of HUVECs combined with fluorescent 1‐μm PS‐MNPs was only 3.80% using flow cytometry analysis. Moreover, there were no significant differences in inflammation, autophagy, reactive oxygen species (ROS) level, lactate dehydrogenase (LDH) release, and adhesion molecule expression following exposure to 1‐μm PS‐MNPs (5, 10, and 25 μg/mL) for 48 h, except for a remarkable decrease in cell viability at the extremely high concentration of 100 μg/mL. Herein, 1‐μm PS‐MNPs showed a low level of acute toxicity to HUVECs in vitro, and we expect these results contribute to the further risk assessment of MNPs on human health. Polystyrene micro(nano)plastics with a diameter of 1 μm (1‐μm PS‐MNPs) interacted weakly with human umbilical vein endothelial cells (HUVECs), and there was no significant effect on autophagy, inflammation, reactive oxygen species (ROS) level, lactate dehydrogenase (LDH) release, and adhesion molecule expression following exposure to 1‐μm PS‐MNPs (5,10, and 25 μg/mL) in HUVECs, except for a detectable decrease in cell viability at extremely high exposure concentration (100 μg/mL).